Dr. Quinn medicine woman. The complete season one [videorecording (DVD)] - Seymour, Jane, 1951-; Allen, Chad, 1974-; Lando, Joe, 1961-; Bean, Orson; Toovey, Shawn (CBS DVD, 2011)
Tales of courage, conviction and romance on the American frontier, as a female doctor arrives in Colorado Springs and adjusts to life in the West.